The effect of summer water stress on the nutritive value of orchard grass (Dactylis glomerata L.) in permanent grassland under increased temperature and elevated atmospheric CO2 - J. Küsters (Elsevier, 2021)
Grassland provides high nutritive forages for ruminants being a main factor in feeding beef and especially dairy cattle. Changes in precipitation patterns, asides rising temperature and CO2 concentration, will severely affect forage species and modify the nutritive value, and this in turn will also impact animal performance. The aim of this study was to evaluate the influence of water stress on agronomic parameters and the nutritive value of orchard grass (Dactylis glomerata L.) in mountainous permanent grassland, under i) ambient (C0T0) and ii) future (C2T2) climate conditions with increased temperature (+3 °C) and elevated CO2 (+300 ppm). To simulate water stress, a drought experiment was conducted during the experimental period. The experiment took place at the Agricultural Research and Education Centre (AREC) Raumberg-Gumpenstein in Styria (Austria) from 2016 to 2018. Experimental plots were harvested in a 3-cut-system and plant samples were analysed for development stage, leaf weight ratio (LWR) and tiller height and weight. The nutritive value was determined by analysing crude protein (CP) and its fractionation, water-soluble carbohydrates (WSC), NDForg, ADForg, metabolizable energy (ME) and digestibility of organic matter (DOM), among others. The results showed that water stress did not alter the development stage of orchard grass, but decreased tiller height and weight under ambient climate conditions. Furthermore, an increase in ME and DOM, and a decrease in NDForg and ADForg occurred under water stress. In combination with elevated temperature and CO2, water stress improved CP, WSC, ME and DOM, and decreased NDForg and ADForg. Conclusively, water stress improved specific nutritive parameters but, in some circumstances, caused a decline in biomass production.